Development of learning materials reading understanding using CIRC in four primary schools - Weni Aulia; Ardipal Ardipal; Darnis Arief (Fakultas Ilmu Pendidikan UNP)
This research is motivated by teaching materials that are used less interest of students to read and not yet contain reading stage (pre-reading, reading and post-reading). The purpose of developing this instructional material is to produce a reading material that is valid, practical, and effective. The type of this research is development research using 4-D model. Based on the validity test obtained percentage of RPP by the expert validator 91.6% and 90.0% practitioner validator. Percentage of teaching materials by 90.6% expert validator and 89.9% practitioner validator. Practicality test of the implementation of RPP obtained percentage of 92.7%. Assessment of teacher responses obtained 93% and assessment of the response learners obtained 89.2% percentage The effectiveness of learning tools learners obtained percentage 81.6%. Assessment of comprehension reading process obtained 75.5% percentage. Based on these results, learning materials to read the understanding using the CIRC model can already be declared valid, practical, and effective.